Process optimization for the manufacture of red rice (Oryza sativa L.) kheer - Kumari, Anjali; Poonia, Amrita (Indian Journal of Dairy Science, 2021)
Red rice contained 13.92±0.13 % moisture, 2.11±0.07 % fat, 1.80±0.01% total ash and 144.45 ± 1.36 (mgGAE/100g) total phenolic content, respectively.  The present study was aimed to prepare kheer using red rice @ 18g (T1), 20g (T2) and 22g (T3). Coconut sugar was used @15 g in all the combinations.  Fresh toned milk (3.0 % fat and 8.5 % SNF) was used with broken red rice (Half broken) grains. Cleaned broken rice was soaked in water (rice to water ratio as 1: 2.5) and cooked at 93°C for about 15 minutes.  Kheer prepared using 20 g of rice (T2) was selected as optimized one on the basis of sensory evaluation. The developed red rice kheer was acceptable upto10 days of storage at refrigerated temperature. Optimized kheer contained 3.02 ± 1.21% fat, 56.16 ± 2.11% moisture and 43.84 ±3.05 % total solids and 356.24± 3.45 Total Phenolic Content (mgGAE/100g).